Soil nutrient and moisture environments and shoot growth of Quercus crispula canopy trees in two areas that experienced contrasting effects of deer overabundance over an 11-year period. Issue 6 (2nd November 2022) - Mizutani, Ayumi; Azuma, Wakana A; Kaneko, Mikoto; Matsuyama, Shuhei
ABSTRACT: To elucidate the effects of modification of the understory aboveground plant biomass and soil nutrient and moisture environments on canopy tree growth in deer overabundance sites, we compared the canopy shoot growth of oak trees ( Quercus crispula ), which are not a target for bark stripping or bark feeding by deer, understory aboveground plant biomass, and components of soil nutrient and moisture between inside (protected) and outside (exposed) a large fenced area. We found that canopy shoot growth in the exposed area was reduced compared with that in the protected area. Net nitrogen (N) mineralization rates did not differ between areas, although understory aboveground plant biomass, total carbon (C) and N, and total soil inorganic N content were significantly lower in the exposed area than in the protected area. Indices of canopy shoot growth correlated significantly with soil water content, but due to the limited scope of our study this result does not confirm an effect of soil moisture on canopy shoot growth. Further study is required to clarify the effects of deer overabundance on canopy tree growth.